The Effect of Corporate Social Responsibility, Managerial Ability, and Tax Planning On Earning Management - Septini Kumalaputri; Dian Kurniawati; Hanifah Setyaningrum (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aimed to obtain empirical evidence of the effect of corporate social responsibility, managerial ability, and tax planning on earning management. Methodology/approach – The data used is obtained from the annual financial statements of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2019. The sample selection method used in this study is the purposive sampling method and the analysis techniques used are descriptive statistics, panel data regression, classical assumption test, and hypothesis test. Data were collected from 51 manufacturing sector companies that met predetermined sample criteria. Findings – The results of this study empirically prove that corporate social responsibility and tax planning have a positive effect on earning management while managerial ability does not affect earning management.